Islamic Education in the Context of the National Education System - Anindya Rizka Ayunda; Meisya Nur Azizah; Opik Taupik Kurahman; Dadan Rusmana (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
This study aims to analyze Islamic education in the context of the national education system. The author emphasizes that Islamic education is an important part of the national education system, so this research generally provides an overview of the Islamic education system in Indonesia. The paper is structured using a qualitative method with a literature review approach. Qualitative research produces information in the form of notes and descriptive data found in the studied texts. The data used is collected from books, journals, and other materials related to the concept of Islamic education within the national education system. The collected data is analyzed using a descriptive method. The research findings indicate that the position of Islamic education within the national education system encompasses formal, informal, non-formal, and religious education. Islamic education in Indonesia is implemented in a planned and systematic manner to develop the potential of students based on Islamic principles and values. It not only studies religious knowledge but has also expanded to include other fields of study.